Analisis Kualitatif Dampak Penerapan Teknologi E-Commerce dalam Peningkatan Pendapatan Kelompok Tani di Kabupaten Kerinci - Sestriyenti, Enny; Ariani, Fatma (Jurnal Pustaka Manajemen (Pusat Akses Kajian Manajemen), 2026)
Digital transformation in the agricultural sector has emerged as a crucial strategy for addressing issues inherent in traditional supply chains. This study aims to analyze in depth the impact of e-commerce technology adoption on increasing the income of farmer groups in Kerinci Regency. Employing a descriptive qualitative approach with a phenomenological design, data were collected through in-depth interviews with farmer group administrators and members, observations, and triangulation with Field Agricultural Extension Officers (PPL). The findings indicate that e-commerce adoption—dominated by social commerce (WhatsApp Business and Facebook Marketplace) and specialized rice e-commerce platforms—significantly cuts out middlemen. Farmers gain greater bargaining power and improved cash flow stability. However, this income growth is still constrained by structural hurdles, such as high logistics costs from Kerinci's highland areas and limited digital literacy among older farmers.